Development of a Prototype for a Product Recommendation System Using Blockchain Technology - Adrian Tri Setiawan; Djarot Hindarto (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Blockchain technology ensures data security and transparency through decentralization and immutability. Smart contracts facilitate automation and foster trust by reducing dependence on intermediaries. Nevertheless, most existing recommendation systems remain centralized, leaving them susceptible to manipulation and security breaches. Although recommendation algorithms are widely used, their application within blockchain-based systems remains limited. By leveraging the Ethereum blockchain and smart contracts, the proposed system enhances transparency, security, and decision-making reliability. The algorithm ranks products based on price, appearance, quality, size, and availability, with results permanently recorded on the blockchain. Experimental findings indicate that the integration of TOPSIS and PROMETHEE II algorithms improves the recommendation process by systematically evaluating multiple criteria. Each product is assessed according to its proximity to both positive and negative ideal solutions, with the final ranking score calculated as the ratio of the negative distance to the total distance (positive plus negative). For example, Pocari Sweat achieved the highest preference score of 0.9619, indicating it is the top recommendation, while Coca-Cola 390ml scored 0.4182, reflecting a lower ranking. These results demonstrate the algorithms’ capacity to distinguish products objectively, supporting accurate and transparent recommendations. The study advances blockchain-based decision support systems by providing secure and transparent recommendation mechanisms. Additionally, the integration of TOPSIS and PROMETHEE II within a blockchain framework demonstrates both feasibility and effectiveness in decentralized environments.